2012
DOI: 10.1212/wnl.0b013e31826aac60
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba does not improve cognitive function in MS

Abstract: Objective: To determine whether Ginkgo biloba extract (ginkgo) improves cognitive function in persons with multiple sclerosis (MS). were randomly assigned to receive either one 120-mg tablet of ginkgo (EGb-761; Willmar Schwabe GmbH & Co, Germany) or one placebo tablet twice a day for 12 weeks. As the primary outcome, we compared the performance of the 2 groups on the 4 tests at exit after adjusting for baseline performance. MethodsResults: Fifty-nine subjects received placebo and 61 received ginkgo; 1 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 26 publications
0
34
1
2
Order By: Relevance
“…Four of these present class I evidence, three studying cannabis22–24 and one studying Ginkgo biloba supplementation 25. The remaining 34 studies present class II evidence (table 1).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Four of these present class I evidence, three studying cannabis22–24 and one studying Ginkgo biloba supplementation 25. The remaining 34 studies present class II evidence (table 1).…”
Section: Resultsmentioning
confidence: 97%
“…It also resulted in a sustained reversal of disability in 12.6% of treated patients, which was significantly more than the control (0 patient). Lovera et al ,25 a class I double-blind RCT analysing 116 participants, found that Ginkgo extract does not have a significant effect on cognitive function compared with a placebo, but is well tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…Study procedures were approved by both 97 sites' Institutional Review Boards. Participants were recruited as part of a previously reported 98 trial comparing the effects of ginkgo biloba versus placebo in individuals with MS. 27 The present 99 data were collected from participants at baseline, prior to randomization. Participants were 100 recruited from both sites' MS clinics, their affiliated university clinics, and their local 101 communities.…”
mentioning
confidence: 99%
“…Future research will also benefit from the inclusion of validity and effort measures, which were not administered in the present study. Third, given the eligibility criteria of the original trial for which the present data were derived (Lovera et al ., ), present results may not generalize to the full MS population. Future studies will benefit from the inclusion of participants across the full spectrum of these measures.…”
Section: Discussionmentioning
confidence: 97%